An Attitude Scale toward Aging and Elderliness: A Validity and Reliability Study - (:unkn) unknown (ISTANBUL UNIV, FAC LETTERS, DEPT SOCIOLOGY, 2016)
The airn of this study.is to conduct the validity and.reliability analysisthe scale developed for measuring the attitudes of adults over 18 toward aging and elderliness. The scale is a five-point LikertHt)Te and self reporting scale. The sample group consists of 842 individuals, all of whom were selected impartially in the city of Istanbul in 2015. As a result of the Factor analyses during the scale's validation, wherein experts were asked their opinions, the scale was identified to consist of 45 items and to contain four factors. The total factor loading has been determined as 57.849; the factors loading values range between 3.119 and 41.2695. According to the results of reliability analysis, Cronbach's Alpha coefficient for the whole scale was calculated as.97. The alpha values for the factors were confirmed to range from.90 to.93. As a result of item analysis, all obtained values for item-total and item-remainder correlations were determined to he significant. (p <.001). Meanwhile, in the discriminant analysis, all items and factors were found discriminative. Test. retest correlations were also found to be significant for the total score (r = 0.89; p <.001). Finally, the scale was found to be usable as a valid and reliable scale for adults 18 and older.
Keywords: Aging; Elderlines; Attitude; Scale; Developing; Validity; Relibility